2020
DOI: 10.1016/j.molliq.2020.113795
|View full text |Cite
|
Sign up to set email alerts
|

Structure of anisole derivatives by total neutron and X-ray scattering: Evidences of weak C H⋯O and C H⋯π interactions in the liquid state

Abstract: High resolution, total neutron and x-ray scattering data have been used in synergy with Molecular Dynamics simulations to access atomistic scale insight into the structure of anisole and 2,3,5trimethylanisole, two aromatic compounds bearing an electron-donating methoxy group. A detailed description is provided for the main interactions occurring in these systems, including π-π stacking and weak hydrogen bonding correlations: C-H•••O and C-H••• π. The existence of preferential orientations of the first shell co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In addition, the classic benzene-benzene interactions seen in the bulk liquids, namely for benzene face-to-face stacking at shorter distances and Y-stacking at longer distances, are maintained in the mixture (Supplementary Fig. 5 ) 24 , 34 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, the classic benzene-benzene interactions seen in the bulk liquids, namely for benzene face-to-face stacking at shorter distances and Y-stacking at longer distances, are maintained in the mixture (Supplementary Fig. 5 ) 24 , 34 .…”
Section: Resultsmentioning
confidence: 96%
“…Previous research on bulk liquids via neutron diffraction has included studies of pure aromatic systems, such as benzene, toluene and anisole, which have revealed the presence of π···π, C-H···π, C-H···O weak interactions 23 , 24 . In the last of these studies, the presence of the electron-donating methoxy group in anisole strongly affects the π cloud while the methyl group of the substituent precludes the possibility of O-H···π bonding.…”
Section: Introductionmentioning
confidence: 99%